Methodological design of a case study research based: innovative learning from the perspective of two technology startups - Gomez Sota, Fátima; Pérez Alfonso, Lorena; Alabau Tejada, Nuria (Journal of Management and Business Education, 2024)
The use of case studies in the classroom, especially in the field of business is a methodology that, since its implementation at Harvard University in the early twentieth century, has focused on active learning not only with respect to the subject matter itself, but also with respect to how to learn to solve problems analytically and critically. It has focused on active learning, not only with respect to the subject of study itself, but also with respect to how to learn to solve real world scenarios from an acute perspective. Nowadays there is a growing need for innovation in business schools based on learning from case studies seeking to reflect the changes and trends of the most contemporary organizations. This article value lies in how a case study of two Valencian technology startups focused on the development and implementation of their innovative organizational culture can be taken to design a case study research based. For its development the traditional stages of a case study are taken as a basis and a triangulation of qualitative and quantitative methods is used. Subsequently, supported on the results obtained, a Harvard Deusto case study research based is designed for its publication and application.